Environmental Issues and Environment Conservation: Addressing the Challenges of Environmental Protection (Journal of Advances and Scholarly Researches in Allied Education, 2021)
“Nature provides a free lunch, but only if we control our appetites.”—William RuckelshausThe word “Environment is most commonly used to describe natural environment and means the sum of all living and nonliving things that surround an organism, or group of organisms. Environment includes all elements, factors, and conditions that have some impact on growth and development of certain organisms. In the recent past the issues pertaining around environmental issues have seen a surge and with the fact, that more than a billion of people live under the dire circumstances of poverty it becomes quite obvious. The biggest problem that prevails is the lack of environmental education been given, the infrastructure of most of the industries are so such they lack the bare minimum parameters. To the shock is the fact there are many laws which any organization has to follow to be friendly with environment but the enforcement of such law becomes difficult with the use of power, corruption and lack of resources. One of the severe most ecological problems which is faced across the globe is is global warming which is often a result of emission of carbon dioxide omitted in the atmosphere by vehicles, large industries etc.